TINJAUAN HUKUM TERHADAP PERKAWINAN BEDA AGAMA YANG DILAKSANAKAN DI LUAR INDONESIA - supriadi M.H (IAIN BONE, 2020)
ABSTRAKThe law number 1 in 1974 about marriage does not allow the existence of interfaith marriage because the system which is allowed in this law is the marriage that is based on law of religion, as stated in section 2 verse 1